The impact of big data predictive analytics on firm performance: the role of cloud ERP and business intelligence integration - Muhassib, Ayman Muhammad Amin (المجلة العلمية للدراسات و البحوث المالية و التجارية : علمية محكمة., 2024)
The purpose of this study was to explore the intangible factors that are essential for a cloud-based Enterprise Resource Planning (ERP) system to be successful. The survey was done on a total of 150 companies in various Egyptian industrial sectors, using a questionnaire list as a data collection instrument. The study hypotheses were tested using both multiple regression analysis and One-Way ANOVA test, as both methods were most suited to the characteristics of this study due to sample size and nature of data. Contrary to expectations, the study findings revealed that Egyptian industrial organizations have a medium level of success, indicating that they have partially succeeded in implementing a cloud-based ERP system. This partially success was driven by top management. the findings also revealed that training and education, workforce commitment, and teamwork are the most critical soft factors (CSFs) required for cloud-based ERP success in the Egyptian environment. finally public sector companies, followed by multinational corporations, were the most influential in terms of implementing cloud-based ERP. الغرض من هذه الدراسة هو استكشاف العوامل غير الملموسة التي تعتبر ضرورية لنجاح نظام تخطيط موارد المشروع القائم على الحوسبة السحابية (ERP based-Cloud). تم إجراء البحث على إجمالي 150 شركة في مختلف القطاعات الصناعية المصرية باستخدام قائمة الاستبيان كأداة لجمع البيانات. تم اختبار فروض الدراسة باستخدام كل من تحليل الانحدار المتعدد واختبار التباين الأحادي (one Way ANOVA)، حيث كانت كلتا الطريقتين الأكثر ملائمة لخصائص هذه الدراسة بسبب حجم العينة وطبيعة البيانات. أظهرت نتائج الدراسة-على عكس التوقعات،-أن المنظمات الصناعية المصرية حققت مستوى متوسط من النجاح، مما يشير إلى نجاحها جزئيا في تطبيق نظام تخطيط موارد المشروع القائم على الحوسبة السحابية. كان هذا النجاح الجزئي مدفوعا بدعم الإدارة العليا. كشفت النتائج أيضا أن التدريب والتعليم، والتزام القوى العاملة، والعمل الجماعي هي أهم العوامل الناعمة (CSFs) المطلوبة لنجاح تخطيط موارد المشروع القائم على الحوسبة السحابية في البيئة المصرية. وأخي را، كانت شركات القطاع العام، تليها الشركات متعددة الجنسيات، هي الأكثر تأثيرا من حيث تطبيق نظام تخطيط موارد المشروع القائم على الحوسبة السحابية.